The analytical credit dataset: A magnifying glass for analysing credit in the euro area - Jean-Marc Israël; Violetta Damia; Riccardo Bonci; Watfe Gibran (European Central Bank (ECB), 2017)
In May 2016 the Governing Council adopted the AnaCredit Regulation (ECB/2016/13) providing the legal basis for the European System of Central Banks (ESCB) to collect granular information on loans from banks to corporates and other legal persons based on a core set of harmonised concepts and definitions. Starting with reference data from September 2018, credit institutions in the euro area, and possibly elsewhere in the EU, will report to the ECB via the national central banks (NCBs) individual credit exposures falling within the reporting scope. The reporting framework is the outcome of in-depth discussions within the ESCB involving several rounds of consultations with users, the industry and other stakeholders. As set out in the Regulation, AnaCredit will, already in Stage 1, significantly enhance the value for analysis on credit and credit risk in the euro area by providing detailed, timely and harmonised information on individual exposures to legal entities as counterparts. The new data will be useful for several key tasks of the ESCB for a better analysis of credit distribution to the economy, e.g. for monetary policy analysis and operation (risk and collateral management), financial stability, economic research and statistics. The scope of the project might be further expanded in future stages to cover additional lenders, borrowers and instruments. The purpose of this paper is to reflect and illustrate the methodological work and process leading to the definition of the AnaCredit requirements that were eventually included in the Regulation.
Keywords: E58; G21; E51; C81; E44; 330; analytical credit dataset; central credit registers; loan-by-loan data; credit risk; central bank statistics